Home improvement. The complete sixth season [videorecording (DVD)] - Finestra, Carmen; McFadzean, David; Williams, Matt, 1964- (Distributed by Buena Vista Home Entertainment, 2007)
Television series revolving around Tim "The Tool Man" Taylor, who has his own television show "Tool Time," and his family. In this season, Tim attempts to break Bob Vila's steamroller record, Jill's wild sisters visit to plan their parents' 50th anniversary, Jill drags Tim to couples therapy, Tim has "the talk" with Brad, Jill's father dies, and Tim delivers Heidi's baby in a gas station.